al-Jamāliyyah al-Uslūbiyyah fī Qaṣīdah Muʾtamar Nahḍah al-‘Ulamā` li al-Kiyāhi al-Ḥājj Afīfuddīn Muhājir: الجمالية الأسلوبية في قصيدة مؤتمر نهضة العلماء للكياهي الحاج عفيف الدين مهاجر - Yaniah Wardani; Suci Ramadhani; Aghnin Khulqi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2024)
This research aims to reveal the contents of the Nahdlatul Ulama Muktamar Poetry written by KH Afifuddin Muhajir. This research uses Syihabuddin Qalyubi's stylistic theory as a tool. This poem is his offering to NU at the 34th Congress in Lampung. The aim of this research is also to try to reveal the beauty of the language of the Qasidah of the NU Congress using five levels, namely phonological, morphological, grammatical, semantic, and imagery theory. This research uses qualitative research with a literature review, namely by reviewing and analyzing data sourced from primary and secondary references that are still related to the topic of discussion. The results of this research prove that in terms of the content of this Qasidah, it includes the poet's praise for NU, the poet's hope for the success of the NU Congress, and the election of the best new leader. Meanwhile, from a stylistic perspective, it was found that qafiyah and bahar were by the content of the qasidah at the phonological level, the use of fi’il forms that were by the meaning of the qasidah at the morphological level, various sentence structures at the grammatical level, the existence of musytarak lafdzi at the semantic level, the discovery of tasybih and majaz at the level of imagery. So, it can be concluded that the language style of this Qasidah is beautiful because it fulfills every stylistic sub-theory.